The Effect of Motivation on Employee Performance - Yeti Kuswati (Budapest International Research and Critics University, 2020)
This research is motivated by the decline of employee performance over a period of time which results in the realization of the work not fully achieving the specified targets. The decline of employee performance is suspected by the decrease in the level of motivation possessed by the employee. The purpose of this study is to empirically prove that motivational factors have an influence on employee performance both descriptively and verifiatively. The research method used is descriptive method and survey method with quantitative data processing and analysis through parametric statistical approaches, the calculation of using SPSS 16 program tools. While the parameters used are employee motivation and performance based on respondents' perceptions with sampling techniques carried out in random sampling. From the research results obtained that the effect of motivation on employee performance is quite good.